1996
DOI: 10.1002/chem.19960020616
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorotaxanes Formed Between Secondary Dialkylammonium Salts and Crown Ethers

Abstract: A very simple self-assembling system, which produces inclusion complexes with pseudorotaxane geometries, is described. The self-assembly of eight pseudorotaxanes with a range of stoichiometries-I : I , 1 :2, 2:1, and 2:2 (host:guest)-has been Keywords achieved. These pseudorotaxanes self-assemble from readily available componentscrown ethers -dialkylammonium well-known crown ethers, such as dibenzo [24]crown-8 and bis-p-phenylene[34lcrown-salts 9 hydrogen bonding -molecular 10, and secondary dialkylammonium he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
238
0
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 347 publications
(265 citation statements)
references
References 109 publications
19
238
0
8
Order By: Relevance
“…Neutral rotaxane monomer 6 was obtained in 84% yield by N-acetylation of 5 with excess acetic anhydride and triethylamine. [35][36][37] The structures of these monomers were determined by 1 H, 13 C NMR and IR spectral analyses along with mass spectra. 1 H NMR spectra of 5 and 6 clearly supported their structures as assigned in Rotaxane-tethering acetylene monomers and side chain-type polyrotaxanes K Nakazono et al presence of syn-anti isomers of the amide group, the spectrum confirmed the rotaxane structure of amide-type rotaxane monomer 6.…”
Section: Monomer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral rotaxane monomer 6 was obtained in 84% yield by N-acetylation of 5 with excess acetic anhydride and triethylamine. [35][36][37] The structures of these monomers were determined by 1 H, 13 C NMR and IR spectral analyses along with mass spectra. 1 H NMR spectra of 5 and 6 clearly supported their structures as assigned in Rotaxane-tethering acetylene monomers and side chain-type polyrotaxanes K Nakazono et al presence of syn-anti isomers of the amide group, the spectrum confirmed the rotaxane structure of amide-type rotaxane monomer 6.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…Splitting of the crown ether oxyethylene proton signals were characteristic of this type of rotaxane, as assigned in Figure 1. 30,[35][36][37] O-Benzylic proton signal, which is sensitive to the position of the crown ether wheel on the axle, moved to 5.9 p.p.m., indicating the localization of the wheel around the ester group. This result suggests that the wheel component gets considerably close to the acetylene moiety in comparison with that of 5.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…Furthermore, blocked-axle 7 was investigated as the chloride salt, which will likely exist in biological environments. In CDCl3, the strong ion pairs greatly weakens pseudorotaxane 8 (KA = 17 ± 0.6 M −1 ) when compared to the typical association observed in the millimolar range for the complex of DB24C8 with R2NH2 + PF6 − salts [24][25][26]. Tighter association was observed in DMSO-d6 (KA = 250 ± 10 M −1 ).…”
Section: Measuring the Stability Of Pseudorotaxanementioning
confidence: 87%
“…The end-cap proceeded efficiently via the Huisgen click reaction with terminal azide- The combination of a 24-membered crown ether, such as dibenzo-24-crown-8-ether (DB24C8), and sec-ammonium salt has been widely used for rotaxane synthesis. 38,42,50 Takata and colleagues [51][52][53] developed various sec-ammonium salt/DB24C8-based rotaxanes and applied them to rotaxane switches in which the mobility and relative position of the rotaxane components could be controlled. Therefore, M2R possessing the sec-ammonium salt/DB24C8 couple can be regarded as an ideal structure-definite polyrotaxane in which the mobility and position of the components should be stimuli responsive.…”
Section: Synthesis Of M2rmentioning
confidence: 99%